Effects of moisture content and temperature on the specific heat of soya bean, Moringa oleifera seed and Mucuna flagellipes nut - Aviara, Ndubisi A.; Ehiabhi, Samuel E.; Ajibola, Obafemi O.; Oni, Surajudeen A.; Power, Pwanzadom P.; Abbas, Thlama; Onuh, Onuh A. (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: The specific heat of soya bean variety TGX 1,440–1E, moringa oleifera seed, moringa oleifera kernel and mucuna flagellipes nut were evaluated and their variations with moisture content and temperature were investigated, using the method of mixture. The specific heat of soya bean, moringa oleifera seed, moringa oleifera kernel and mucuna flagellipes nut increased linearly from 1 780 to 2 646 J/(kg·K), 1 520 to 2 516.121 J/(kg·K), 1 625.24 to 2 458.214 J/(kg·K) and 2 080 to 4 586 J/(kg·K) in the moisture content and temperature ranges of 6.16%–51.52% (d.b.) and 305.8–363 K, 8.43%–31.66% (d.b.) and 300–341.88 K, 6.75%–31.5% (d.b.) and 300–344.38 K, and 3.38%–10.7% (d.b.) and 300–330.75 K, respectively. While the specific heat of soya bean increased with increase in temperature up to a certain point and decreased with further increase in temperature, the specific heat of moringa oleifera seed and kernel increased linearly, and mucuna flagellipes nut exhibited a second order polynomial relationship between its specific heat and average temperature. Regression models, which could be used to reasonably predict the specific heat of these products at specified moisture content and average temperature, were established. Key words: soya bean var. TGX 1,440-1E, moringa oleifera, mucuna flagellipes, specific heat, moisture content, temperature DOI: 10.3965/j.issn.1934-6344.2011.01.087-092 Citation: Ndubisi A Aviara, Samuel E Ehiabhi, Obafemi O Ajibola, Suradeen A Oni, Pwanzadom P. Power, Thlama Abbas, et al. Effect of moisture content and temperature on the specific heat of soya bean, Moringa oleifera seed and Mucuna flagellipes nut. Int J Agric & Biol Eng, 2011; 4(1): 87<span style="font-size: 9pt; line-height: 140%; font-family: